Beyond borders: cystic fibrosis survival between Australia, Canada, France and New Zealand. Issue 3 (15th September 2022) - Coriati, Adèle; Ma, Xiayi; Sykes, Jenna; Stanojevic, Sanja; Ruseckaite, Rasa; Lemonnier, Lydie; Dehillotte, Clémence; Tate, Jan; Byrnes, Catherine Ann; Bell, Scott C; Burgel, Pierre Regis; Stephenson, Anne L
Abstract : Background: Life expectancy for people with cystic fibrosis (CF) varies considerably both within and between countries. The objective of this study was to compare survival among countries with single-payer healthcare systems while accounting for markers of disease severity. Methods: This cohort study used data from established national CF registries in Australia, Canada, France and New Zealand from 2015 to 2019. Median age of survival for each of the four countries was estimated using the Kaplan-Meier method. A Cox proportional hazards model was used to compare risk of death between Canada, France and Australia after adjusting for prognostic factors. Due to low number of deaths, New Zealand was not included in final adjusted models. Results: Between 2015 and 2019, a total of 14 842 people (3537 Australia, 4434 Canada, 6411 France and 460 New Zealand) were included. The median age of survival was highest in France 65.9 years (95% CI: 59.8 to 76.0) versus 53.3 years (95% CI: 48.9 to 59.8) for Australia, 55.4 years (95% CI: 51.3 to 59.2) for Canada and 54.8 years (95% CI: 40.7 to not available) for New Zealand. After adjusting for individual-level factors, the risk of death was significantly higher in Canada (HR 1.85, 95% CI: 1.48 to 2.32; p<0.001) and Australia (HR 2.08, 95% CI: 1.64 to 2.64; p<0.001) versus France. Interpretation: We observed significantly higher survival in France compared with countries with single-payer healthcare systems. The median age of survival in France exceeded 60 years of age despite having the highest proportion of underweight patients which may be due to differences in availability of transplant.